Analisis Penerapan Pembelajaran Berdiferensiasi dalam Implementasi Kurikulum Merdeka pada Pelajaran Seni Rupa di SDN 5 Banawa - Zafira Safitri; Kadek Hariana; Rizal Rizal; Surahman Surahman (JURNAL DIKDAS, 2025)
This study aims to describe the implementation of differentiated learning in the context of the Merdeka Curriculum in Fine Arts lessons at SDN 5 Banawa. This research is a qualitative descriptive study. The subjects of this study include the school principal, four teachers, and 26 fourth-grade students. Data collection techniques used in this study include observation, questionnaires, interviews, and documentation. The data were analyzed using data reduction, data presentation, and conclusion drawing. The data validity was tested using source triangulation. The results of the study indicate that the implementation of differentiated learning in the Merdeka Curriculum for Fine Arts at SDN 5 Banawa has been carried out effectively. The fourth-grade teacher has successfully identified students' learning styles and addressed their learning needs. Students were grouped according to their characteristics, interests, and talents. Differentiated learning was carried out through several stages, such as initial assessment, preparation of teaching materials, and grouping students based on their abilities. The majority of students agreed that group learning met their learning needs.